2012
DOI: 10.1159/000336378
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Therapies: A Potential Role in Perinatal Medicine

Abstract: Pregnancies complicated by impaired placentation, acute severe reductions in oxygen supply to the fetus, or intrauterine infection are associated with oxidative stress to the mother and developing baby. Such oxidative stress is characterized as an upregulation in the production of oxidative or nitrative free radicals and a concomitant decrease in the availability of antioxidant species, thereby creating a state of fetoplacental oxidative imbalance. Recently, there has been a good deal of interest in the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 169 publications
1
70
0
1
Order By: Relevance
“…Antioxidant therapy may prevent or ameliorate brain tissue damage following hypoxia [19,20,21,22]. In support of this proposal, we have shown that the administration of melatonin prior to an acute hypoxic event in the late gestation sheep fetus abolishes both the primary and secondary increases in brain hydroxyl radical formation and reduces cerebral lipid peroxidation [23].…”
Section: Introductionmentioning
confidence: 87%
“…Antioxidant therapy may prevent or ameliorate brain tissue damage following hypoxia [19,20,21,22]. In support of this proposal, we have shown that the administration of melatonin prior to an acute hypoxic event in the late gestation sheep fetus abolishes both the primary and secondary increases in brain hydroxyl radical formation and reduces cerebral lipid peroxidation [23].…”
Section: Introductionmentioning
confidence: 87%
“…Much research has been devoted into antenatal therapies to improve placental blood flow, e.g., sildenafil (83), or to reduce oxidative stress by the use of antioxidants, e.g., melatonin (84). These therapies may offer potential new treatment strategies to ameliorate the negative effects of chronic fetal hypoxia on the developing cardiovascular system.…”
Section: Prenatal Interventionmentioning
confidence: 99%
“…This developmental difference could help explain the correlation between greater cerebral immaturity and worse impairment after TBI. [5][6][7][8][9][10][11][12][13][14] Docosahexaenoic acid (DHA) is a candidate neuroprotectant that decreases neuroinflammation in the adult rat. 15 DHA is an essential nutrient for normal brain function and development and is the most abundant omega-3 polyunsaturated fatty acid (22:6n-3) in the mammalian brain.…”
mentioning
confidence: 99%